Sociodemographic, clinical, and environmental determinants of tuberculosis and diabetes mellitus comorbidity: A case-control study - Syahti, Fitri Dwi; Nursal, Dien Gusta Anggraini; Djafri, Defriman (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Tuberculosis-Diabetes Mellitus comorbidity poses a major challenge in controlling communicable and non-communicable diseases simultaneously. TB-DM comorbidity represents a significant health concern, as both conditions can mutually influence one another, necessitating focused attention in clinical management, prevention, and treatment strategies. Therefore, it is essential to investigate how sociodemographic, clinical, and environmental factors contribute to the prevalence and severity Purpose: To explore how sociodemographic, clinical, and environmental factors contribute to the prevalence and severity of tuberculosis-diabetes mellitus comorbidity. Method: A quantitative research with a case control matching study research design. This study used secondary data from the tuberculosis information system of the West Sumatra Provincial Health Office. Samples were taken as many as 830 people with a ratio of cases (Tuberculosis-Diabetes Mellitus) and controls (Tuberculosis) 1:1. Data collected were comorbidity status of tuberculosis-diabetes mellitus and tuberculosis, sociodemographic, clinical and environmental data. Data were analyzed by univariate, bivariate, multivariate. Results: Univariately, there were 830 cases of tuberculosis-diabetes mellitus comorbidity and 830 cases of tuberculosis. Age ≥ 45 (81.45%), employment (62.53%), urban residential area (47.21%), health facility referral (12.77%), type of pulmonary tuberculosis (98.3%), history of tuberculosis relapse (10.72%). There was an association between age, occupation, type of tuberculosis, and history of tuberculosis treatment with tuberculosis-diabetes mellitus comorbidity (p<0.05). There was no association between residential area and referral status with the incidence of DR-TB comorbidity (p>0.05). The most dominant risk factor for tuberculosis-diabetes mellitus comorbidity was age with p-value=0.0001 with OR=11.031 (95% CI 8.0143-15.185). Conclusion: Age tends to be the risk probability for tuberculosis-diabetes mellitus comorbidity compared to tuberculosis. It is recommended that routine screening for diabetes mellitus be carried out in tuberculosis patients, especially in the age group ≥ 45 years because this group has the highest risk of experiencing tuberculosis-diabetes mellitus comorbidity.